The Cross-border Insolvency Provision as Ius Contituendum of Bankruptcy Act of Indonesia - Andrian, Andrian; Lie, Gunardi (Law Development Journal, 2024)
The lack of cross-border insolvency regulation in Indonesia is an issue that hasn't been resolved until now. Borderless business patterns that developed continuously resulted in the promulgation of cross-border insolvency regulations becoming increasingly urgent. Even more, Indonesia as a member state of ASEAN must be fully aware that currently there is a process of economic integration in ASEAN as outlined in the ASEAN Economic Community Blueprint. In consequence, harmonious cross-border insolvency regulations are needed. Philippines, Singapore, and Myanmar already had cross-border insolvency regulation through the adoption of the UNCITRAL Model Law on Cross-border Insolvency while Indonesia still stuck to territorialism approach, not only in cross border insolvency proceeding, but also in civil proceedings in general. Indonesia has to synchronize civil code, civil procedural code, international civil code, and bankruptcy code to create legal certainty in bankruptcy law system. Therefore, in this article writing, there are several approaches that will be used, namely the comparative approach and statutory approach, with the research method of normative juridical. The objectives to be achieved in this article are to construct the lack of cross-border insolvency regulation in Indonesia and to describe cross-border insolvency regulation and practices in Philippines, Singapore, and Myanmar. At the end of this article, there is a recommendation to the Indonesian Government to immediately regulate cross-border insolvency in Indonesia, either by adoption of Model Law or by mutual agreement with certain countries.